Certainty Equivalence, First Order Certainty Equivalence, Stochastic Control, and the Covariance Structure - Young, Richard M. (Econometrica, 1975)
[This paper is concerned with clarifying the relationship between the certainty equivalence and first order certainty equivalence results. The effects of applying the first order certainty equivalence result are examined by analyzing the effects on the control vector of a one period stochastic control problem of a change in elements of the covariance matrix of parameters.]